Vocalizations, Distribution, and Ecology of the Cloud-Forest Screech Owl (Megascops marshalli) - Herzog, Sebastian K.; Ewing, Steven R.; Evans, Karl L.; MacCormick, Aidan; Valqui, Thomas; Bryce, Rosalind; Kessler, Michael; MacLeod, Ross (The Wilson journal of ornithology, 2009)
The poorly known Cloud-forest Screech Owl (Megascops marshalli) is a Peruvian endemic known from only two localities, and its vocalizations have not been documented. We report the first Bolivian specimen and sound-recordings, an analysis of the species' longsong in comparison with other brown-eyed Andean screech owls, and discuss its distribution, natural history, ecological relationships with sympatric congeners, and conservation status. Longsongs were most similar to those of the allopatric Cinnamon Screech Owl (M. petersoni) in northern Peru and Ecuador. Principal component analysis of four vocal characters identified: (1) notable overlap between the two species; (2) some overlap of the Cloud-forest Screech Owl with Ecuadorian, but not with sympatric Bolivian populations of the Rufescent Screech Owl (M. ingens); and (3) considerable, evidently clinal geographic variation in the Rufescent Screech Owl. Divergence in vocal characteristics between the Cloud-forest Screech Owl in Bolivia and other species decreased with increasing geographic distance. The Cloud-forest Screech Owl is now known from six localities from Departamento Pasco, Peru, south to Departamento Cochabamba, Bolivia, and has a disjunct distribution with four subpopulations and an overall extent of occurrence of ∼12,700 km2. Its preferred habitat is pristine to at most slightly disturbed wet montane forest with high structural complexity, dense understory, and abundant epiphytes. It has been recorded at altitudes of 1,550–2,580 m, but locally its altitudinal range is ∼500 m, where it is narrowly syntopic with Rufescent Screech Owl at its lower and White-throated Screech Owl (M. albogularis) at its upper terminus. Narrowly overlapping altitudinal replacement in Andean Megascops taxa combined with variable location of replacement zones depending on local ecoclimatic conditions suggest that species' distributions are primarily maintained by exclusion via interspecific competition. The Cloud-forest Screech Owl is currently properly listed as Near Threatened, but further research may show it is more appropriately categorized as Vulnerable.